The perspective on congruence within a teaching-learning environment among 2nd and 3rd year Sports Science bachelor students - Rica Wium Geiker , Nina; Petursson Gunnarsson, Thomas (Improving University Science Teaching and Learning, 2023)
A university course can be viewed upon as a “teaching-learning system” (Hounsell & Hounsell, 2007). That system functions optimally when intended learning outcomes (ILO’s) are of high-quality and matched in harmony with teaching styles and assessment, which was described as constructive alignment by Biggs (Biggs, 1996; Biggs & Tang, 2003). From a student perspective, a constructive alignment between learning outcomes, teaching and assessment styles is imperative in university courses, as inconsistencies may lead to student disappointment/frustration which in turn may lead to lack of motivation and learning outcomes that are diminished compared to those intended.